Can NT-proBNP be used as a criterion for heart failure hospitalization in emergency room? - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2011)
BACKGROUND: Heart failure is a common health problem with poor prognosis. The gold standard for diagnosis is echocardiography but it is not always reachable, especially in emergency conditions. NT-pro-brain natriuretic peptide (NT-proBNP) is a novel indicator for the diagnosis of heart failure and is being used in routine tests in emergency rooms. This study was conducted to compare NT-proBNP levels between hospitalized congestive heart failure (CHF) patients and outpatients. METHODS: This study was designed as a single-centre, prospective, and controlled trial. Blood samples and data were collected from a total of 119 patients with shortness of breath admitted to Department of Emergency, School of Medicine, Marmara University. Patients were primarily diagnosed with decompensated heart failure according to the Framingham criteria and aged above 18 years. A total of 92 patients were included in the study after exclusions. NT-proBNP measurements were made by immune fluorescent method. Available data were compared between hospitalized patients and outpatients. RESULTS: NT-proBNP levels were significantly higher in hospitalized patients compared to outpatients, and this finding was correlated with the clinical status of the patients. The mean NT-proBNP value of the patients was 9741.9 +/- 8973 pg/ml (range: 245-35000) while the mean NT-proBNP value of patients diagnosed with non-decompensated congestive heart failure was 688.9 +/- 284.5 pg/ml (range: 115-1450.65). CONCLUSIONS: NT-proBNP can be used as an easy diagnostic method for congestive heart failure. A certain cut-off value may be determined in further multi-centre controlled trials with larger patient groups.
Keywords: NT-Pro-Brain Natriuretic Peptide; Heart Failure; Emergency; BRAIN NATRIURETIC PEPTIDE; DIAGNOSIS; DYSPNEA; MANAGEMENT; ACCURACY; BNP